Impact of the Coronavirus disease 2019 and the post-pandemic construction sector (Pakistan). Issue 4 (2nd November 2021) - Ayat, Muhammad; Ullah, Azmat; Kang, Chang Wook
Abstract : Purpose: The coronavirus disease (COVID-19) pandemic has negatively affected project management organisations especially those conducting large construction projects that involve a large number of people, complex supply chains, and lack of experience and preliminary arrangements in managing remote work. This study aims to analyse the impact of COVID-19 on the construction sector and how to minimise the effect of pandemic disruptions. Design/methodology/approach: This study is based on the reviews of relevant reports, articles and semi-structured interviews of the construction experts working in the Pakistan construction industry during the current COVID-19 pandemic. The primary data for this study were collected through semi-structured interviews with the construction experts and analysed them using thematic analysis. A total of 15 semi-structured interviews were conducted in this study. Findings: Through thematic analysis, this study identified approximately 55 initial raw data themes, 15 first-order themes, 11 second-order themes and 4 general dimensions of the impact of COVID-19 on the construction sector. The authors identified working style and behavioural changes, challenges and risks, stakeholders and new directions for the construction sector in the post-pandemic world as the four main dimensions of the effect of the pandemic on the construction sector. Further, least digitalisation, complex cash flow, abundance of labour-intensive methods, diverse stakeholders, and dependencies on foreign expertise, imported material and machineries were identified as the most important reasons for poor resiliency of the construction sector during COVID-19 pandemic in Pakistan. Originality/value: This study major contributions are: (1) analysing the impact of COVID-19 on the construction sector in relation to Pakistan, (2) discussing new directions for the construction sector and (3) putting in place a set of mitigation measures that will help minimise disruptions in construction-related projects to ensure that set objectives are achieved.